2020
DOI: 10.4103/jfmpc.jfmpc_868_20
|View full text |Cite
|
Sign up to set email alerts
|

Role of Faith healers: A barrier or a support system to medical care- a cross sectional studyRole of faith healers: A barrier or a support system to medical care, a cross sectional study

Abstract: Background and Aims: Faith healing is a method of treating illnesses through the exercise of faith rather than medical methods. The current study was done with the objective to find out demographic variables of faith healers, various conditions for which the people approach them, various practices and processes used and to look for scope of integrated approach to healthcare with faith healers. Settings and Design: RHTC village was a sub center village of PHC Morad. Henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…More than 90% of our respondents favored treatment by faith healers as opposed to other fact-findings (19-34%) 2,10,11,14,16 . According to Sharma et al, integrating spiritual healing traditions and medical practitioners at the local level may aid in early referral and the beginning of appropriate therapy 31 .Most of our surveyees believed in surgical treatment for epilepsy, similar to a work by Santhosh NS 7 . Nonetheless, in other investigations, the majority were unaware of the same 13,18,27,30 .…”
Section: Discussionsupporting
confidence: 58%
“…More than 90% of our respondents favored treatment by faith healers as opposed to other fact-findings (19-34%) 2,10,11,14,16 . According to Sharma et al, integrating spiritual healing traditions and medical practitioners at the local level may aid in early referral and the beginning of appropriate therapy 31 .Most of our surveyees believed in surgical treatment for epilepsy, similar to a work by Santhosh NS 7 . Nonetheless, in other investigations, the majority were unaware of the same 13,18,27,30 .…”
Section: Discussionsupporting
confidence: 58%
“…It represents the practice of treating illness through prayers, rituals, and the exercise of faith. 54 In a recent study conducted in Ghana, 55 researchers deduced that the trust in faith healers and positive perception of them is quite high. Faith healers reported that they provide flexibility in terms of location and time to people and that this could be one of the reasons why people are prone to approach them more freely.…”
Section: Patient-related Processesmentioning
confidence: 99%
“… 56 This might lead to delayed treatment-seeking and delayed contact with the medical healthcare professional, which may result in adverse outcomes. 55 For this reason, it has been suggested that faith healers and formal medical institutions could consider working in tandem. 55 , 56 This strategy could be useful for preventive and curative purposes, although the literature lacks insights on the relationship between faith healing and the PA of terminal patients.…”
Section: Patient-related Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…[17,18] Incense sticks and incense are generally used to purify the environment with fragrances on various occasions like marriages, rituals, funerals, ghost festivals, and other religious activities, especially in Southeast Asian countries. [19][20][21] The smoke released from incense and incense sticks burning may alleviate an allergic response in some people, via inhalation of micron and submicron particles that cause pulmonary disorders via aggravated oxidative stress. [9,22,23] Earlier numerous investigators have shown the adverse effects of the incense smoke from houses and temples.…”
Section: Introductionmentioning
confidence: 99%